The water resource implications of changing climate in the Volta River Basin [Africa]. - McCartney, Matthew P.; Forkuor, Gerald; Sood, A.; Amisigo, B.; Hattermann, F.; Muthuwatta, Lal P. (International Water Management Institute, 2012)
The Volta River is one of the major rivers in Africa. A transboundary basin, which is the principal water source for approximately 24 million people in six riparian states, it is likely to experience increasing stress in the near future as a consequence of both greater water demand and climate change. In a study to ascertain the joint impacts of changes in demand and supply within the basin, a dynamic regional climate model (CCLM), a hydrological model (SWAT) and a water resource model (WEAP) were used to provide an assessment of the possible implications of one downscaled middle impact (i.e., lying between extremes) climate change scenario on the performance of existing and planned irrigation and hydropower schemes. The models were used to simulate the climate change in tandem with four scenarios, each reflecting different levels of water resources development as indicated in the plans of the riparian states. It is not possible to quantify the error arising from the models in combination and the results should be considered indicative rather than absolute. Nonetheless, they provide a useful indicator of possible future change and have important implications for water resource planning. The results indicate that, by the middle of the twenty-first century, basin-wide average annual rainfall, mean annual runoff and mean groundwater recharge, will all decline. These changes significantly undermine the technical performance of existing and planned reservoirs, which, in turn, affects development outcomes. In the intermediate development scenario, climate change is anticipated to reduce average annual hydropower generation by approximately 30% and increase average annual unmet irrigation demand four-fold by the middle of the century. By the end of the century and in the full development scenario, the reduction in technical performance of reservoirs is even greater. Therefore, even though investment in reservoirs brings benefits, these benefits are significantly reduced in comparison to those that would accrue in the absence of climate change. The changes are likely to have dire consequences for economic development, food security and poverty in the region. Against this background, water resources development in the basin requires interventions that bolster resilience and water security. This necessitates much more systematic planning of water storage, greater cooperation between the riparian states and consideration of innovative approaches to water storage, such as managed aquifer recharge.